Diabetes awareness: Significant knowledge gap among medical and nursing students in Delhi - Pragya Mangla, Nishant Raizada, Harleen Kaur, Sri Venkata Madhu (South Eastern European Journal of Public Health, 2025)
Background: Diabetes is a public health problem in India. Assessing and supplementing the knowledge and awareness about diabetes, its risk factors and its basic management is crucial in primary, secondary and tertiary prevention of diabetes. Objective: To assess the knowledge of diabetes in medical and nursing students through a questionnaire based survey in a tertiary teaching hospital in Delhi. Methodology: A validated diabetes awareness and knowledge (DAK) questionnaire was administered to medical and nursing students in their early years of training. Basic demographic information was noted. Results: Filled questionnaires of total 314 students of medical (31.4% females) and nursing (100% females) training at entry [M0 (98) and N0 (62) respectively] and after 1 year of training [M1 (109) and N1 (45) respectively] was analyzed. Median (IQR) age was 20 (2) years. Median score of medical students was higher than nursing students (30.3/50 vs 28/50; p=0.003). Medical and nursing students had comparable DAK scores at their entry and significantly higher scores after 1 year of training [M0 26.0 vs M1 35.0 and N0 24.7 vs N1 31.0; p<0.001 for both]; more in medical students than nursing students (M1 35.0 vs N1 31.0; p<0.001). All students had low scores in questions on basics of diabetes; lower in nursing students than the medical students; lower in entry years than after 1 year of training. Conclusion: Medical and nursing students had ‘low’ level of diabetes knowledge at entry and ‘moderate’ level after 1 year of training while remaining short of what is desirable.